(untitled) (Journal of Comparative & International Higher Education, 2023)
The COVID-19 pandemic posed significant disruptions in traditional educational policies and practices worldwide. The study adopted an equity, diversity, and inclusion lens to investigate the impact of the pandemic on international students in a Canadian university. The findings from data analysis identified challenges and supports for international students in five areas: academic, financial, health and well-being, socialization, and housing and accommodation. There were several gaps between international students’ academic and social needs during the pandemic and the institutional support. While the university prioritized supports in the academic domain, international students identified social challenges as more significant during the pandemic. The gap was also evident in communicating institutional support to students, as some students were not aware of the spectrum of institutional services. Finally, there was a need for more targeted support for international students. The pandemic called for more fundamental and comprehensive actions to support the diverse student population.